2016
DOI: 10.2134/cftm2015.0205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Date on Distribution of Seasonal Forage Yields in Dual‐Purpose Wheat, Oats, and Ryegrass Crops

Abstract: Planting date is a key factor for determining the forage yields in different seasons to meet grazing requirements for various winter annual crops. The main objective of this study was to evaluate the effect of planting date on seasonal forage yield distribution for different grazing systems in dual-purpose winter wheat (Triticum aestivum L.), oats (Avena sativa L.), and ryegrass (Lolium multiflorum L.). The research was conducted in two consecutive growing seasons (2003-2004 and 2004-2005) at the Texas A&M U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 12 publications
4
16
1
Order By: Relevance
“…Between-year and between-site variability in the benefits of intercropping have been attributed to environmental conditions, with greater benefits observed in semiarid environments [14]. At 2 Mg DM ha −1 , aboveground biomass yield of oat sown in late summer and harvested in the autumn in this study (Table 2) was somewhat less than that reported by others for late summer sown oat [19,20,29]. The mid-summer-sown oat in the present study was headed when harvested.…”
Section: Overseeded Forage Biomasscontrasting
confidence: 56%
See 2 more Smart Citations
“…Between-year and between-site variability in the benefits of intercropping have been attributed to environmental conditions, with greater benefits observed in semiarid environments [14]. At 2 Mg DM ha −1 , aboveground biomass yield of oat sown in late summer and harvested in the autumn in this study (Table 2) was somewhat less than that reported by others for late summer sown oat [19,20,29]. The mid-summer-sown oat in the present study was headed when harvested.…”
Section: Overseeded Forage Biomasscontrasting
confidence: 56%
“…As with the brassicas evaluated by others [16,17], earlier planting increased autumn forage yield of winter cereals compared to later planting [20].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…1). Delaying planting until late November (PD6) reduced the forage production compared with earlier planting dates, consistent with Lyon et al (2001) and Darapuneni et al (2016), where forage yields were reduced for the winter and early‐spring harvest as planting date was delayed. Moreover, late planting may also result in poor root growth (Winter and Musick, 1993).…”
Section: Planting Date Effect On Forage Yieldsupporting
confidence: 53%
“…Although these stress factors are predominant for wheat planted in late summer or early fall, these earlier planting dates do allow for wheat plants to produce more fall and winter forage to be consumed by grazing animals. A study conducted in central Texas reported that planting dual‐purpose wheat in early September maximized the fall forage production; in contrast, the winter and spring forage yields were maximized by planting between late October and early November (Darapuneni et al, 2016). Beyond early November, there was a consistent decrease in forage yield.…”
Section: Planting Date Effect On Dual‐purpose Wheat Productionmentioning
confidence: 99%